SELF-SUSTAINED POWER FOR MOBILE DEVICES: A STEPPER MOTOR-DRIVEN SOLUTION - Teleron, Jerry I.; Leonen, Jeffrey T.; Galang, Christian Louis M. (International Journal of Engineering Science Technologies, 2023)
This study introduces a self-sustained power solution for mobile devices using a stepper motor-driven mechanism. The objective is to ensure reliable power supply during critical situations when traditional sources are unavailable. A prototype device was designed and experimentally evaluated. The device utilizes a stepper motor as a generator, converting mechanical energy into electrical energy through a hand crank. A full bridge rectifier transforms the generated alternating current into direct current compatible with mobile devices. A battery serves as the primary power storage, enabling energy accumulation. Experimental testing verified the device’s performance. Mobile devices, including cellphones, laptops, and routers, were connected to assess charging capabilities. The results demonstrated successful charging, providing dependable power during outages and inaccessible charging methods. The findings establish the stepper motor-driven self-sustained power device as a practical emergency power solution. It empowers individuals to maintain communication channels and power mobile devices during critical situations, enhancing resilience. Its versatility and portability ensure effectiveness in diverse locations where conventional power sources are unreliable. In conclusion, this study presents a novel self-sustained power solution employing a stepper motor-driven mechanism. Experimental results confirm its capability to charge mobile devices, supporting communication and resilience during emergencies. The device has significant potential to benefit individuals and communities, providing reliable power and improving emergency response and communication capabilities.